Characterizing individual differences in children and adolescents with autism spectrum disorder: a descriptive study - Di Vara, S.; Guerrera, S.; Menghini, D.; Scibelli, F.; Lupi, E.; Valeri, G.; Vicari, S. (Frontiers in Psychology, 2024)
Introduction Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by a higher prevalence in male than in female participants. Recent studies have hypothesized the presence of different phenotypes in male and female participants with ASD. The present study aims to assess possible sex differences in cognitive and adaptive functioning, symptomatology of ASD, and psychopathological comorbidities in a large sample of children and adolescents with ASD. Methods The study included a total of 2,146 children and adolescents diagnosed with ASD, comprising 1785 boys (mean age 7.12 ± 3.69 years) and 361 girls (mean age 6.25 ± 3.30 years). The age of the participants ranged from 1.35 to 19.05 years (mean age 9.98 ± 3.64). The study sought to include all children and adolescents diagnosed with Autism or ASD. Results Present results showed that girls with ASD had lower IQs than boys but similar adaptive functioning. The severity of symptoms of ASD was greater in boys than in girls, as were scores on psychopathological measures. With increasing age, boys with ASD showed greater impairment in social communication skills than girls and increased psychopathological comorbidities. Older girls showed fewer restricted and repetitive behaviors. Discussion Exploring phenotypic differences in children and adolescents with ASD fosters an understanding of subtle diagnostic facets that may go unrecognized, allowing for increasingly individualized and tailored interventions.